2017
DOI: 10.1016/j.ultrasmedbio.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cranial Ultrasound: Are Current Safety Guidelines Appropriate?

Abstract: Ultrasound can lead to thermal and mechanical effects in interrogated tissues. We reviewed the literature to explore the evidence on ultrasound heating on fetal and neonatal neural tissue. The results of animal studies have suggested that ultrasound exposure of the fetal or neonatal brain may lead to a significant temperature elevation at the bone-brain interface above current recommended safety thresholds. Temperature increases between 4.3 and 5.6°C have been recorded. Such temperature elevations can potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
(95 reference statements)
0
28
0
2
Order By: Relevance
“…There are 2 programs for Australian operators that are formulated to specifically address education in neonatal cranial ultrasound. One is the Certificate of Clinician‐Performed Ultrasound, which is the model for training and accreditation for neonatal cranial ultrasound in Australia and New Zealand . However, the curriculum for the Certificate of Clinician‐Performed Ultrasound qualification covers all aspects of ultrasound, with a major emphasis on functional echocardiography and assessment of line position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 2 programs for Australian operators that are formulated to specifically address education in neonatal cranial ultrasound. One is the Certificate of Clinician‐Performed Ultrasound, which is the model for training and accreditation for neonatal cranial ultrasound in Australia and New Zealand . However, the curriculum for the Certificate of Clinician‐Performed Ultrasound qualification covers all aspects of ultrasound, with a major emphasis on functional echocardiography and assessment of line position.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound can lead to thermal and mechanical effects in interrogated tissues. We have recently reviewed the literature in this field, and the results of animal studies have suggested that ultrasound exposure of the fetal or neonatal brain may lead to a substantial temperature elevation at the bone‐brain interface . Mean temperature increases between 4.3 °C and 5.6 °C have been observed in utero with guinea pigs and mature mice as animal models .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…На відміну від дорослих і дітей старшого віку, у немовлят завдяки незарощеному великому тім'ячку є перфектне ультразвукове вікно, що дає змогу широко використовувати ультразвукову нейросонографію в поєднанні з допплерівським вимірюванням швидкостей кровотоку в мозкових судинах. Власне ультразвукове вивчення структури головного мозку вже дає неоціненну інформацію щодо морфології мозку, наявності набряку мозкових тканин, ступеня їх диференційованості, симетричності, наявності осередків ішемії й крововиливів [45].…”
Section: амплітудно-інтегрована електроенцефалографіяunclassified
“…is most commonly used to diagnose IVH (1,9) . In premature infants, IVH almost exclusively presents within the rst ve days of life, with 50, 25, 15, and 10 % of cases occurring on the rst, second, third, and fourth and beyond days of life (DOL) (6,10) .…”
Section: Introductionmentioning
confidence: 99%